Regulating sex for sale: prostitution policy reform and the UK - Phoenix, Joanna (Policy Press, 2009)
Frameworks of understanding / Jo Phoenix -- What's anti-social about sex work? Governance through the changing representation of prostitution's incivility / Jane Scoular [and others] -- Community safety, rights, redistribution and recognition: towards a coordinated prostitution strategy? / Maggie O'Neill -- UK sex work policy: eyes wide shut to voluntary and indoor sex work / Teela Sanders -- Out on the streets and out of control? Drug-using sex workers and the prostitution strategy / Margaret Melrose -- Male sex work in the UK: forms, practice and policy implications / Mary Whowell and Justin Gaffney -- Beyond child protection: young people, social exclusion and sexual exploitation / Jenny Pearce -- From 'toleration' to zero tolerance: a view from the ground in Scotland / Ruth Morgan Thomas